Expedient Assembly of Bioactive Maleic Anhydrides Using Click Diels–Alder Chemistry - Boukouvalas, John; Thibault, Charles; Loach, Richard P. (Synlett, 2014)
A versatile pathway to substituted maleic anhydrides is illustrated by the synthesis of the nanomolar FTase inhibitor chaetomellic anhydride A, a germination promoter, and a novel bis-anhydride cross-linking reagent for cell or tissue fixation. Starting from commercial or easily prepared alkynes, these targets were assembled in two steps by click–unclick oxazole–alkyne cycloaddition–cycloreversion and furan oxyfunctionalization.
Keywords: alkynes; click chemistry; furans; natural products; oxazoles; total synthesis